Effects of a robot‐aided somatosensory training on proprioception and motor function in stroke survivors - Yeh, I-Ling; Holst-Wolf, Jessica; Elangovan, Naveen; Cuppone, Anna Vera; Lakshminarayan, Kamakshi; Capello, Leonardo; Masia, Lorenzo; Konczak, Jürgen (Journal of neuroEngineering and rehabilitation, 2021)
Proprioceptive deficits after stroke are associated with poor upper limb function, slower motor recovery, and decreased self-care ability. Improving proprioception should enhance motor control in stroke survivors, but current evidence is inconclusive. Thus, this study examined whether a robot-aided somatosensory-based training requiring increasingly accurate active wrist movements improves proprioceptive acuity as well as motor performance in chronic stroke.
Gesehen am 10.06.2021